85.4k views
5 votes
Which equation represents h(x)?

h(x) = 3x - 2
h(x) = 3x + 2
h(x) = 3x - 2
h(x) = 3x + 2

Which equation represents h(x)? h(x) = 3x - 2 h(x) = 3x + 2 h(x) = 3x - 2 h(x) = 3x-example-1
User Weberik
by
4.7k points

2 Answers

2 votes

Answer: B is correct

Have a blessed day.

User Jdnoon
by
5.4k points
6 votes

Answer:

Explanation:

You might find this easier if you change h(x) to y. It might look more familiar.

you are given 1 point and that is (-1,1). What that means is when x = -1,

y = 1

You have written this as though y is linear. It is not. The power is 1/3, not 1.

Let us try B which is what I think the answer is.

y = (x + 2)^(1/3)

Put x = -1 on the right hand side.

y = (-1 + 2)^(1/3)

y = (1)^(1/3)

The cube root of 1 is 1.

So the answer is

y = (x + 2)^(1/3)

User Wcolbert
by
5.2k points